The effects of preoperative pregabalin administration on postoperative pain on Libyan patients undergoing laparoscopic cholecystectomy - Munira Elmansouri; Aisha Dugani; Salah Adala (Libyan International Medical University Journal)
Objective: The present prospective study was carried out in Surgical Department of Tripoli Central Hospital with the aim to evaluate the effect of preoperative single dose of 150 mg pregabalin in reducing postoperative pain and analgesic consumption after laparoscopic cholecystectomy. Patients and Methods: Sixty patients of both sexes in the age of 18–60 years undergoing laparoscopic cholecystectomy were randomly allocated into two equal groups of 30 patients each. The pregabalin group received 150 mg oral pregabalin 1 h before induction of anesthesia and a placebo group received a matching placebo orally. Variables measured included age, sex, body mass index (BMI), duration of surgery, time to first dose and total dose of meperidine after recovery, and the visual analog scale (VAS – static and dynamic). The occurrence of nausea and vomiting during the first 24 h postoperative was also recorded. Results: No significant difference was found between the meperidine and the placebo groups regarding age, sex, BMI, or duration of surgery. The time of first meperidine dose required to alleviate pain after surgery was significantly four times longer in the pregabalin group as compared to the placebo group. The total dose of meperidine required for pregabalin group was significantly lower than that required for placebo group. Moreover, VAS was significantly decreased in the pregabalin group compared to placebo group both at static and dynamic states only 1 h after recovery. Conclusion: This study validates the preoperative use of a single dose of pregabalin in attenuating pain intensity postoperatively and reducing total analgesic consumption.